Acute Coronary Stent Infection With Pseudoaneurysm Formation and Stent Separation After Percutaneous Coronary Intervention - Malin Renee Flygel, MD; Nigusssie Bogale, MD, PhD; Steinar Lundemoen, MD, PhD; Rafael Alexander Leiva, MD; Terje Hjalmar Larsen, MD, PhD; Sahrai Saeed, MD, PhD; Robert Mantongo Persson, MD; Anja Oksnes, MD (JACC: Case Reports)
Clinical Condition: We present a case of an extremely rare condition of acute stent infection in a patient with multiple previous coronary interventions who underwent a successful percutaneous coronary intervention for chronic total occlusion with stent implantation in his right coronary artery. He developed fever the day after the procedure, and blood culture showed growth of Staphylococcus aureus. Positron emission tomography–computed tomography showed fluorodeoxyglucose uptake in relation to the right coronary artery stent, and follow-up computed tomography showed the development of a pseudoaneurysm and suspicion of stent separation. Key Questions: Is the S aureus bacteremia in his blood culture related to the procedure? What do positron emission tomography–computed tomography findings indicate? Can the devolvement of a pseudoaneurysm cause stent separation? Outcome: After a broad multidisciplinary discussion and fear of pseudoaneurysm rupture with lethal outcomes, a successful open-heart surgery was performed, involving the removal of the pseudoaneurysm and stents. The patient is currently doing well with only mild symptoms. Take-Home Messages: The current work highlights the importance of close surveillance of patients presenting with signs and symptoms of septicemia after coronary intervention. It also underscores the value of a broad and dynamic multidisciplinary discussion and action during the management of such a rare complication with mycotic coronary aneurysms.